2014
DOI: 10.3389/fnbeh.2014.00408
|View full text |Cite
|
Sign up to set email alerts
|

Medial prefrontal cortex dopamine controls the persistent storage of aversive memories

Abstract: Medial prefrontal cortex (mPFC) is essential for initial memory processing and expression but its involvement in persistent memory storage has seldom been studied. Using the hippocampus dependent inhibitory avoidance learning task and the hippocampus-independent conditioned taste aversion paradigm together with specific dopamine receptor agonists and antagonists we found that persistence but not formation of long-term aversive memories requires dopamine D1/D5 receptors activation in mPFC immediately after trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
1
34
0
Order By: Relevance
“…3c) [171]. Importantly, inhibition of neuronal activity and protein synthesis in the mPFC 12 h after fear learning has been shown to impair remote LTM assessed 7 days, but not recent LTM tested 2 days after training [177]. Similar to results from dorsal CA1 in the HPC [178], this study reported that remote, but not recent LTM is modulated by D1/D5 dopaminergic receptors in the mPFC 12 h after training.…”
Section: A Sleep-dependent Window For Remote Ltm Consolidation?supporting
confidence: 66%
“…3c) [171]. Importantly, inhibition of neuronal activity and protein synthesis in the mPFC 12 h after fear learning has been shown to impair remote LTM assessed 7 days, but not recent LTM tested 2 days after training [177]. Similar to results from dorsal CA1 in the HPC [178], this study reported that remote, but not recent LTM is modulated by D1/D5 dopaminergic receptors in the mPFC 12 h after training.…”
Section: A Sleep-dependent Window For Remote Ltm Consolidation?supporting
confidence: 66%
“…Because of the well-established role of DA in memory consolidation (1721) we hypothesized that DA may control generalization by ensuring the precise consolidation of conditioned threat responses. Using a mouse behavioral paradigm for auditory threat response generalization, we observed that DA controls generalization through concomitant activation of D2 type receptors (D2R) in both the CEA and BNST.…”
Section: Introductionmentioning
confidence: 99%
“…In support to this, intra-PFC infusion of dopamine D1, amino-hydroxymethyl-iso xazole propionate (AMPA) and glutamate N-methyl-Daspartate (NMDA) receptor antagonists or infusion of camino-butyrate type A (GABA A ) agonist were shown to interfere with aversive memory consolidation at distinct time windows. This effect was significant when applied at different time-points between 1.5 and 12 h after fear conditioning (Souza et al, 2000;Izquierdo et al, 2007;Gonzalez et al, 2014). In particular, blockade of D1 receptors in the medial PFC 6 h after training disrupts the long-term retrieval of a step-down inhibitory avoidance memory (Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This effect was significant when applied at different time-points between 1.5 and 12 h after fear conditioning (Souza et al, 2000;Izquierdo et al, 2007;Gonzalez et al, 2014). In particular, blockade of D1 receptors in the medial PFC 6 h after training disrupts the long-term retrieval of a step-down inhibitory avoidance memory (Gonzalez et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation